ANALYSIS OF FACTORS CAUSE DELAY PROJECT CONSTRUCTION BRIDGE IN THE CITY OF BANJARMASIN - Isramaulanan, Aulia; Yuliana, Candra; Hasbullah, Hasbullah (TROPICAL WETLAND JOURNAL, 2017)
With an area of 98.46 km2 whose territory is separated by rivers, to increase economic growth Banjarmasin City has done infrastructure development in the field of transportation of roads and bridges are quite significant. But in the process of implementation, there is often a delay in the bridge construction project. This can lead to problems within the scope of the project itself. So it is necessary to do further research to know the cause of the bridge construction project delay. This research is conducted qualitatively and quantitatively. The causative factors obtained from the literature were distributed to contractors through questionnaires to see perceptions of contractors and concessions. The data of the questionnaire were analyzed by using validity test, reliability, and descriptive statistical analysis with Pearson Moment (Bivariate Pearson) method assisted by ms. excel to get the factors causing the delay. Then the delay factors will be tested through interviews with stakeholders in the three bridge samples. Based on the results of data processing analysis, it can be concluded that the factors that greatly affect the bridge construction project delays are analyzed by descriptive analysis of material arrival delay, material arrival delay, damage due to negligence of work, and work that does not comply with operational standards